Study of middle ear fluid pH and pepsinogen 1 level in childhood otitis media - Kamide, Yosuke (Pediatric Otorhinolaryngology Japan, 2011)
To investigate the extent of involvement of pathological gastroesophageal reflux in the development of childhood otitis media, the pH of the fluid in the middle ear at various stages of otitis media of 39 children aged 0 to 13 years old (median age, 2 years and 5 months) who had undergone tympanostomy between June 2009 and January 2010 was measured, and the amount of pepsinogen 1 (PG1) in the fluid was also quantitated. The pH was measured using a Horiba compact pH meter (B-211). PG1 was measured at 450 nm using an ELISA kit with a human PG1-specific monoclonal antibody. Measurement of the middle ear fluid pH revealed an average pH of 7.86 (SD±0.56). When a PG1 concentration of 100 μg/l in the retained fluid in the middle ear was defined as the cutoff value and lower levels were defined as negative, positive results (values of 100 μg/l or over) were obtained in 41% of the patients (16/39 cases). The average pH level in the negative group was 8.04 (SD±0.43), while that in the positive group was 7.54 (SD±0.50), and the difference in pH between the two groups was significant. There was a significantly higher number of children aged 2 years or over in the positive group. The results suggested pathological gastroesophageal reflux in 41% of the subjects with childhood otitis media. Measurement of the middle ear fluid pH levels may be useful for determining the presence of pathological gastroesophageal reflux.